Was the Gibson Paradox for Real? A Wicksellian study of the Relationship between Interest Rates and Prices - Jagjit S. Chadha; Morris Perlman (University of Kent, School of Economics, 2014)
We examine the relationship between prices and interest rates for seven advanced economies in the period up to 1913, emphasizing the UK. There is a significant long-run positive relationship between prices and interest rates for the core commodity standard countries. Keynes (1930) labelled this positive relationship the 'Gibson Paradox'. A number of theories have been put forward as possible explanations of the Paradox but they do not fit the long-run pattern of the relationship. We find that a formal model in the spirit of Wicksell (1907) and Keynes (1930) offers an explanation for the paradox: where the need to stabilise the banking sector's reserve ratio, in the presence of an uncertain 'natural' rate, can lead to persistent deviations of the market rate of interest from its 'natural' level and consequently long run swings in the price level.
Keywords: B22; E12; E31; E42; 330; disability; Gibson's Paradox; Keynes-Wicksell; Prices; Interest Rates